Mobile apps for students with autistic spectrum disorders - Argyriadis, Alexandros; Argyriadi, Agathi (My University, 2017)
For children with autism, using a mobile phone or a computer in the educational process is an efficient alternative educational strategy, on one hand because children show skill in using computers, and on the other hand, because symbols and images are intriguing to them. This chapter focuses on the use of mobile phones in the learning process and particularizes on students with autism. It presents steb by step the creation of a mobile application through a specific example, hoping to trigger further teachers' engagement with new technologies.
Keywords: Autism; Children; Mobile phone; Mobile application